2009
DOI: 10.3109/10641950802601278
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised, Double-Blinded, Placebo-Controlled Study of the Phosphodiesterase Type 5 Inhibitor Sildenafil for the Treatment of Preeclampsia

Abstract: We have safely conducted a clinical trial of a drug not routinely used during pregnancy. Sildenafil in the escalating dose regimen 20-80 mg tid was well tolerated, with no increase in maternal or fetal morbidity or mortality but did not prolong pregnancy duration in women with preeclampsia. (ClinicalTrials.gov number, NCT 00141310).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
154
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 20 publications
5
154
0
1
Order By: Relevance
“…Sildenafil also increased blood flow to the fetal-placental hypertension. It is therefore not surprising that in a small clinical trial, sildenafil given to women with established preeclampsia was not associated with improvement in pregnancy outcomes (42). Furthermore, since preeclampsia is a very heterogeneous disease, it may be critical to focus therapeutic studies with sildenafil specifically in subgroups of patients who have augmented circulating sFLT1 and increased pressor response to Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil also increased blood flow to the fetal-placental hypertension. It is therefore not surprising that in a small clinical trial, sildenafil given to women with established preeclampsia was not associated with improvement in pregnancy outcomes (42). Furthermore, since preeclampsia is a very heterogeneous disease, it may be critical to focus therapeutic studies with sildenafil specifically in subgroups of patients who have augmented circulating sFLT1 and increased pressor response to Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil citrate (Viagra), a phosphodiesterase-5 inhibitor known to improve blood flow via cyclic guanosine monophosphate (cGMP)-mediated endothelial relaxation of blood vessels, enhanced vasodilatation of myometrial small arteries from women with FGR. 6 Oral or subcutaneous sildenafil citrate in randomized controlled trials in human FGR and PET have shown no maternal or neonatal benefit, 17 although a recent small nonrandomized study did show significantly increased abdominal circumference in severe early-onset FGR 18 but no benefit on fetal outcome. It is concerning that in pregnant ewes carrying growth-restricted fetuses, intravenous infusion of sildenafil citrate decreased uterine blood flow causing fetal hypoxia, probably because of a systemic reduction in vascular resistance and consequent blood flow 'steal' from the uteroplacental circulation to the systemic vascular circuit.…”
Section: Introductionmentioning
confidence: 99%
“…ruled out any teratogenic effect implicated with Sildenafil use [22]. Similarly reassuring data comes from studies where Sildenafil was used as an adjunct to infertility treatment [14,23]. Furthermore the adverse effects appear to be the extended side effects of the drug and are not potentially threatening, but are sufficient enough to reduce drug acceptability.…”
Section: Discussionmentioning
confidence: 99%